A Study of Request Strategies used by EFL Baturaja University Students: Studi Strategi Permintaan yang digunakan oleh Siswa Pendidikan Bahasa Inggris Universitas Baturaja - Mila Arizah - (Edukasi Lingua Sastra, 2021)
Abstract: The problem in this study contents is about the request strategies used by ESL Baturaja University Students. The aim of this study was to determine the most common request strategies used by EFL Baturaja University students. In this analysis, the descriptive approach was used as the research methodology. The study had 80 student population. The sample of the study was 22 that were taken by cluster random sampling taken from English students of English education study program in academic 2020/2021. For collecting the data writer was used a discourse completion test (DCT). Based on the result of the data showed that in the discourse completion test (DCT) regarding the strategy requests used by students. So the result was as much as 16.55°/c student responses used direct strategies, as many as 8 I .81/c student responses used conventionally indirect, and as many as I .62°/c student responses used Non- conventionally indirect. lt means t hat, the dominant request strategies used by EFL was t he conventionally indirect.